P–120 Selecting spermatozoa with the highest genomic integrity in order to enhance clinical outcomes in men with high DNA fragmentation levels. (6th August 2021) - Tavares, D; Xie, P; Haddad, M; Rosenwaks, Z; Palermo, G D
Abstract: Study question: What are the best methods of selecting spermatozoa with the highest genomic integrity in order to improve embryo implantation and term pregnancy rates with ICSI? Summary answer: Testicular or ejaculate spermatozoa isolated by microfluidic sperm selection (MFSS) were characterized by superior genomic integrity with improved clinical pregnancy and delivery rates. What is known already: In couples with unexplained infertility, a subtle male factor can often be identified. Both single-strand (ss) and double-strand (ds) DNA nicks and breaks hinder the ability of the male gamete to support embryonic development. Surgical retrieval of spermatozoa from the proximal male genital tract can prevent their exposure to oxidative stress. Moreover, use of membrane-based microfluidics chips has been shown to allow for selection of the most progressively motile spermatozoa with higher genomic integrity. Study design, size, duration: Over the course of 48 months, 86 consenting men presenting with high sperm chromatin fragmentation (SCF) in their ejaculate with prior ART failure underwent a subsequent cycle with specimens retrieved by testicular biopsy or ejaculate processed by MFSS. A concurrent TUNEL assay was performed on samples collected or selected by each method. Sperm specimens of both origins were utilized for ICSI cycles. Semen parameters, chromatin integrity, and pregnancy outcomes were compared between the two methods. Participants/materials, setting, methods: Fresh ejaculates from consenting men were collected for standard semen analysis (WHO 2010). Testicular biopsy and MFSS were used to isolate spermatozoa with a higher genomic integrity after previous ART failure. SCF was assessed by terminal deoxynucleotidyl transferase dUTP nick-end labeling (TUNEL) on at least 500 spermatozoa under a fluorescent microscope with a threshold of ≥ 15%. MFSS was carried out by Zymot® chips. ICSI was performed in the standard fashion. Main results and the role of chance: A total of 86 men (36.5±5 years) had the following semen parameters: volume of 2.6 ±1mL, concentration of 27.0±33 x 106/mL, 35.6±15% motility, and high SCF (24.1±10%). They underwent 146 ICSI cycles with their partners (maternal age, 33.7±3) resulting in a high incidence of pregnancy loss (100%; 13/13). Of those who failed to conceive, 22 couples used surgically retrieved spermatozoa (SRS) with a concentration of 1.8 ± 4 x 106/mL (P < 0.01), 5.0±11% motility (P < 0.01), and an SCF of 12.6 ± 6% (P < 0.0001). SRS was used in 37 ICSI cycles, yielding a fertilization rate of 61.6% (204/331, P < 0.01), an implantation rate of 10.6% (9/85, P < 0.01), a CPR of 23.5% (8/34, P < 0.01), and a delivery rate of 17.6% (6/34, P < 0.01). Another 24 couples underwent ICSI cycles with ejaculated spermatozoa processed by MFSS with a concentration of 1.8±3 x 106/mL (P < 0.01), but an increased motility of 99±1% (P < 0.01) and an SCF of 1.2 ±1%, lower than both the raw and testicular specimens (P < 0.0001). MFSS-processed specimens resulted in a fertilization rate of 76% (335/441, P < 0.01), an implantation rate of 26.3% (15/57, P < 0.05), and a CPR of 67.9% (19/28, P < 0.01), of which 15 patients delivered and 2 pregnancies are ongoing (89.5%; P < 0.01). Limitations, reasons for caution: This is a preliminary study on a small number of subjects. A randomized prospective study conducted on a larger cohort would be required to confirm our findings. Wider implications of the findings: SCF severely affects pregnancy by impairing embryonic development, consequently promoting implantation failure. While retrieving spermatozoa from the germinal epithelium is a viable option, MFSS provides an alternative. Although MFSS requires an adequate number of sperm with good kinetic characteristics, it provides a more palatable option, reducing surgical risk and costs. Trial registration number: Not applicable